A recent challenge in structural steel design: progressive collapse - Ergüçlü, Erdem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Progressive collapse is a structural design challenge which was discovered 45 years ago but gained awareness in recent years. It is defined by ASCE 7-05 as the spread of an initial local failure from element to element resulting, eventually, in the collapse of an entire structure or a disproportionate large part of it. In this study two case studies have been considered in order to illustrate progressive collapse analysis of steel braced frames. Relevant design codes from USA, Canada and Europe; and also recent papers have been reviewed in order to provide a broad literature that enhances intelligibility of the case studies. In the first case study, progressive collapse potential of two ten-story prototype steel braced frames have been investigated. These were a Special Concentrically Braced Frame (SCBF) and an Eccentrically Braced Frame (EBF) designed previously for different seismic design categories. Alternate Path Method (APM) introduced by recent progressive collapse specific design codes like UFC 4-023-03 have been utilized. Accordingly, nonlinear dynamic time history analysis have been carried out after removing critical column and associated braces from models at different story levels. Here, element removals simulated initial local failure due to an abnormal event. Analysis results revealed that SCBF has progressive collapse potential at the last two stories whereas EBF has collapse potential at the first three stories. The results of nonlinear dynamic analysis were used in the second case study to investigate the accuracy of Dynamic Increase Factor (DIF) calculated per UFC. This factor is used to represent dynamic nature of progressive collapse in APM with Nonlinear Static Analysis (NSA). The use of the equation suggested by UFC for NSA of braced frames needs further investigation since for some removal cases it has underestimated the DIF.
Keywords: Structural engineering.; Steel, Structural.